Blockchain Technology as Economic Infrastructure: Revisiting the Electronic Markets Hypothesis - Berg, Chris; Davidson, Sinclair; Potts, Jason (Frontiers in Blockchain, 2019)
In the late 1980s and early 1990s the electronic markets hypothesis offered a prediction about effect of information technology on industrial organisation, and many business writers forecast significant changes to the shape and nature of the firm. However, these changes did not come to pass. This paper provides an economic analysis of why, using the transaction cost economic framework of Ronald Coase and Oliver Williamson. Non-hierarchical corporate organisation struggled against contracting problems in the presence of possible opportunistic behaviour. Technologies of trust offer an institutional mechanism that acts on the margin of trust, suppressing opportunism. The paper concludes that blockchain technology provides an economic infrastructure for the coordination of economic activity and the possible realisation of the electronic markets hypothesis.